1992
DOI: 10.1182/blood.v80.11.2883.bloodjournal80112883
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor/interleukin-3 fusion protein (pIXY 321) enhances high-dose Ara-C-induced programmed cell death or apoptosis in human myeloid leukemia cells

Abstract: High dose Ara-C (HIDAC) induces programmed cell death (PCD) or apoptosis in vitro in human myeloid leukemia cells, which correlates with the inhibition of their clonogenic survival. Hematopoietic growth factors (HGFs) granulocyte-macrophage colony-stimulating factor (GM- CSF) and interleukin-3 (IL-3) have been demonstrated to enhance the metabolism and cytotoxic effects of HIDAC against leukemic progenitor cells. We examined the effect of pIXY 321 (a GM-CSF/IL-3 fusion protein) on HIDAC-induced PCD and related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Thus, we generated adenoviral vectors expressing two additional hypothetical IL‐12 family heterodimers not yet found naturally, termed IL‐Y (p40 and p28) and IL‐X (Ebi3 and p19), as single chain molecules. Other studies have shown that single chain fusions of G‐CSF and GM‐CSF and G‐CSF and IL‐3 are biologically active and that single chain IL‐12 and Il‐23 are as or more active than the normal dimeric cytokine . Our analysis suggests that IL‐Y in particular is able to stimulate a specific subset of cytokines/chemokines, distinct from the IL‐12 family members.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, we generated adenoviral vectors expressing two additional hypothetical IL‐12 family heterodimers not yet found naturally, termed IL‐Y (p40 and p28) and IL‐X (Ebi3 and p19), as single chain molecules. Other studies have shown that single chain fusions of G‐CSF and GM‐CSF and G‐CSF and IL‐3 are biologically active and that single chain IL‐12 and Il‐23 are as or more active than the normal dimeric cytokine . Our analysis suggests that IL‐Y in particular is able to stimulate a specific subset of cytokines/chemokines, distinct from the IL‐12 family members.…”
Section: Discussionmentioning
confidence: 49%
“…The anti‐tumor activities of IL‐12 and IL‐23 also were significantly enhanced when their two subunits were expressed as a single chain using a 15 amino acid linker . The enhanced function of the linked cytokines is reminiscent of previous studies with IL‐12 (p35 and p40), G‐CSF (GM‐CSF fusion), and GM‐CSF (IL‐3 fusion) .…”
Section: Introductionmentioning
confidence: 59%
“…It has been demonstrated that expression of Bcl‐2, an antiapoptotic protein, is increased following short‐term phorbol ester treatment in the immature Ramos B‐cell line, and up‐regulation of expression of Bcl‐2 increases cell resistance to apoptosis [24, 25]. In HL‐60 cells, induction of apoptosis by ara‐C has been shown to be associated with down‐regulation of Bcl‐2 [26]. However, apoptosis induced by photosensitization is a rapid process, which does not require new protein synthesis [4].…”
Section: Discussionmentioning
confidence: 99%
“…DNA from both supernatant and pellet was precipitated by addition of 1 N perchloric acid. The DPA method (Bhalla et al, 1992) was used for measurement of DNA content. The percent change of DNA fragments was calculated with the following equation:…”
Section: Quantitative Analysis Of Fragmented Dnamentioning
confidence: 99%